2017
DOI: 10.1182/blood-2017-06-791228
|View full text |Cite
|
Sign up to set email alerts
|

Ixazomib significantly prolongs progression-free survival in high-risk relapsed/refractory myeloma patients

Abstract: • IRd was associated with a consistent PFS benefit vs placebo-Rd in RRMM patients with high-risk and standardrisk cytogenetics. • The addition of ixazomib toRd overcomes the poor PFS associated with high-risk cytogenetics in patients with RRMM.Certain cytogenetic abnormalities are known to adversely impact outcomes in patients with multiple myeloma (MM). The phase 3 TOURMALINE-MM1 study demonstrated a significant improvement in progression-free survival (PFS) with ixazomib-lenalidomide-dexamethasone (IRd) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 39 publications
2
72
0
4
Order By: Relevance
“…Studies in relapsed patients of the novel proteasome inhibitors carfilzomib and ixazomib also support this concept with a benefit over the control arm of the relevant studies in high-risk patients but continued suboptimal outcomes compared with standard-risk patients. 70,71 More recently, tandem autologous transplant, posttransplant consolidation, and maintenance have all proved effective for newly diagnosed high-risk patients compared with standard of care 72 and may to some extent attenuate unfavorable outcomes, but no strategy to date is able to completely overcome the adverse effect of high-risk lesions. Prospective recruitment of high-risk patients to dedicated protocols is needed.…”
Section: Prognostic Biomarkers At Different Disease Time Pointsmentioning
confidence: 99%
“…Studies in relapsed patients of the novel proteasome inhibitors carfilzomib and ixazomib also support this concept with a benefit over the control arm of the relevant studies in high-risk patients but continued suboptimal outcomes compared with standard-risk patients. 70,71 More recently, tandem autologous transplant, posttransplant consolidation, and maintenance have all proved effective for newly diagnosed high-risk patients compared with standard of care 72 and may to some extent attenuate unfavorable outcomes, but no strategy to date is able to completely overcome the adverse effect of high-risk lesions. Prospective recruitment of high-risk patients to dedicated protocols is needed.…”
Section: Prognostic Biomarkers At Different Disease Time Pointsmentioning
confidence: 99%
“…The novel triplet IRD (ixazomib, lenalidomide, dexamethasone) has been approved in more than 70 countries for patients with relapsed and refractory multiple myeloma (RRMM) based on the results of several clinical trials including TOURMALINE-MM1 (NCT01564537). [1][2][3][4][5][6][7][8] The results of clinical trials, however, are usually not representative of the typical "real-world" patient in the community setting; the population recruited to these studies is subject to signi cant selection bias which utilizes inclusion and exclusion criteria to predominantly enroll less pre-treated and healthier patients, usually with better overall life expectancy. 9,10 This prospectivaly de ned analysis of the Czech Registry of Monoclonal Gammopathies (RMG) will present real-world clinical outcomes for patients with RRMM treated in routine clinical practice in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…The HR for all the 172 patients' PFS was 0.781 (95%CI, 0.492-1.240, p = 0.293) in favor of IRd and the medians were 15.4 months vs. 11.3 months in the IRd vs. placebo-Rd groups, respectively. And in this study, we can see that in patients with isolated Amp1q21, a improvement of PFS benefit from IRd was obvious in 20% and 60% cutoffs (HR: 0.682 and 0.683, respectively), and showed a poor results in 3% cutoff (HR: 0.781; 95% CI: 0.492-1.240) [17].…”
Section: Data Extraction and Citations Presentationmentioning
confidence: 50%
“…A group of studies have showed that bortezomib can improve complete response, progression-free survival (PFS), and overall survival (OS) in t (4; 14) and Del (17/17p) [15,16]. And for the patients with Amp1q21, there are also some studies proved that the bortezomib and ixazomib may be effective, but the evidence is still not sufficient [17][18][19]. In this study, we will integrate all available evidence, describe the statement of the treatment for MM patients with Amp1q21 and compare all the regimens in this study to explore an optimum therapy for these patients.…”
Section: Ivyspring International Publishermentioning
confidence: 99%